Effects of an education reform on household poverty and inequality: A microsimulation analysis on the free Senior High School policy in Ghana - Kwabena Adu-Ababio; Robert Darko Osei (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The level of income can be directly inferred from the level of education, making education an important variable as a key determinant of better livelihoods and poverty alleviation. However, in most developing countries education is not accessible to all. In Ghana - although basic education is largely free - for secondary education this was not the case until recently. Hence, the high tuition fees and other scholarly expenses continue to be a burden on parents and guardians. The problem was further compounded when government subsidies to upper secondary institutions were delayed. It is not surprising that the government has decided to provide this service as a public good to the benefit of all. In the 2017/2018 academic year the government began an educational reform policy to fully absorb the cost of Senior High School and vocational education for any student who qualifies. Seeing this as a form of benefit to households, this study provides an analysis of the effect of the reform on household poverty and inequality. Analysis is based on the Ghana Microsimulation Model which has the Ghana Living Standards Survey - Round 6 as its base input data. Results provide policy makers with some good ex-ante evidence on the extent to which the reform is contributing to lessening the burden of vulnerable households.
Keywords: D61; H23; H31; O12; 330; education reform; microsimulation; GHAMOD; poverty